FAKTOR – FAKTOR YANG MEMPENGARUHI PEMBERIAN SUSU FORMULA PADA BAYI YANG DIRAWAT DI RUANG NIFAS RSUP PROF. DR. R. D. KANDOU MANADO - Susanto, Hery; Wilar, Rocky; Lestari, Hesti (e-CliniC, 2015)
Abstract: Increased formula feeding was caused by lack of knowledge about the benefits of breastfeeding, low education, aggressive promotion of infant formula, and support from health care professionals. The are several cases where the infants given formula due to several conditions, like mother is unable to produce milk, small amount of milk production, absence of nipple appearance, post-op pain, pain during breastfeeding. The following study aims to determine what factors affecting Giving Infant Formula Milk Treated in Postpartum Room Prof. Dr. R. D. Kandou Hospital Manado. This study is a descriptive design with direct interview approach. The population in this research were all treated in the maternal postpartum Prof. Dr. R. D. Kandou Hospital Manado. Conclusion: The results obtained from 50 respondents show that 66% has a good knowledge about the benefits of breastfeeding, 66% says that health care professional support given infant formula, 100% says that their closest relatives support given breastfeeding, 34% is affected the promotion of infant formula, and 34% are women without complaints of breastfeeding hindrance factor. This study recommends that mothers / parents cooperate with health care professionals cooperation in order to increase the success rate of breastfeeding. Keywords: infant formula, breastfeeding Abstrak: Meningkatnya pemberian susu formula disebabkan pengetahuan kurang mengenai manfaat ASI, pendidikan yang rendah, agresifnya promosi susu formula, dukungan petugas kesehatan. Adapun bayi yang diberikan susu formula karena beberapa kondisi ibu yang mengeluh tidak keluarnya ASI, ASI kurang, puting tidak muncul, sakit bekas operasi, nyeri saat menyusui. Penelitian ini bertujuan untuk mengetahui Faktor-Faktor Apa yang mempengaruhi Pemberian Susu Formula pada Bayi yang Dirawat di Ruang Nifas RSUP Prof Dr. R. D. Kandou Manado. Penelitian ini bersifat deskriptif dengan pendekatan wawancara langsung. Populasi dalam penelitian ini adalah seluruh ibu melahirkan dirawat di ruang nifas RSUP Prof Dr. R. D. Kandou Manado. Kesimpulan: Hasil penelitian yang diperoleh dari 50 responden diketahui bahwa 66% pengetahuan baik mengenai manfaat ASI, 66% petugas kesehatan mendukung pemberian susu formula, 100% orang terdekat mendukung pemberian ASI, 34% terpengaruh promosi susu formula, 34% kondisi ibu dengan tanpa keluhan. Penelitian ini merekomendasikan agar ibu/orang tua dengan petugas kesehatan adanya kerjasama dalam keberhasilan pemberian ASI. Kata kunci: susu formula, ASI